A labelling system improves parental comfort and willingness to use topical corticosteroids for paediatric atopic dermatitis. Issue 1 (29th December 2020) - Wilson, F.; Harnik, E.; Gore, C.
Abstract: Objectives: In the United Kingdom, atopic dermatitis (AD) affects 20% of children and topical corticosteroids (TCS) are a mainstay of AD treatment regimes. Many TCS have similar packaging despite significant differences in potency frequently leading to confusion, and along with misinformation and steroid phobia, potentially reducing treatment adherence. We aimed to evaluate parents' knowledge/concerns regarding TCS and explore benefits of/preference for a TCS‐labelling system. Method: Hundred parents of children with AD attending paediatric dermatology and/or allergy appointments completed mixed‐methodology Survey 1 (knowledge‐quiz, TCS‐labelling options, feedback on what supports AD‐care). Thirty parents, adolescents, and healthcare professionals completed Survey 2. Qualitative/quantitative data was thematically/statistically analysed (SPSS v25) respectively. Results: Parents preferred the traffic light system (green = mild, yellow = moderate, red = potent; n = 71/100) and reported significantly increased willingness and comfort in using TCS if a labelling system was used p ≤ 0.001). Knowledge regarding TCS potency was lacking: 62% ( n = 46/74) of mild TCS‐users overestimated potency; 51% ( n = 67/131) of potent TCS‐users underestimated potency. Common concerns were TCS‐related skin thinning, long‐term side effects and themes for improved AD‐care/support included: better information, written plans, access to advice, involvement of certain staff. Parents wanted accessible information in various formats: verbally, electronic resources, leaflets, and education sessions. Conclusions: Parents of children with AD confirmed significant concerns and demonstrated poor knowledge regarding TCS use. Our findings suggest that a simple labelling system may improve TCS adherence. Future work to test refined label prototypes and evaluating their impact on adherence and correct use is needed.